KOMUNIKASI SIBER PADA FENOMENA CAPTION "TWITTER, PELASE DO YOUR MAGIC!" DALAM MENUMBUHKAN AKSI MENOLONG ANTAR NETIZEN - Nahdah Salsabila Fammy, (2020)
Th Forms of cyber communication on Twitter social media there are various ways to attract the attention of readers or just get retweets and likes from other Twitter users. One of them by using the caption "Twitter, please do your magic!". This study aims to determine the process of communication on social media communication processes on Twitter social media in fostering a helping-help movement between Twitter users. This study uses a descriptive qualitative approach with the interview method to obtain data, in-depth interviews were chosen to obtain data from the point of view of the source. This research uses the CMC (Computer Mediated Communication) theory because it discusses the existence of a communication process mediated by an internet-based computer, where communication in social media uses the internet to spread and receive information. The results of this study prove that the use of Twitter was chosen for sharing information containing invitations to help because Twitter is a social media that is considered to be fast and effective in spreading information, especially in terms of help. In addition, there are differences in the perceptions of each resource person to get the experience that he feels directly. This research also proves that help can still be done well even though only through cyber media, especially social media Twitter, one of the efforts made is to use features in Twitter itself such as retweets and likes and comments in spreading information. Research is expected to provide knowledge about communication on social media for specifically regarding the use of the caption "Twitter, please do your magic!".